N – alkanes in molluscs of Shatt Al-Arab river - Farid, W.A.; Al-Saad, H.T.; Al-Adhub, A.H.Y. (Mesopotamian Journal of Marine Sciences, 2022)
This study comprises monitoring of the n-alkanes in the Shatt Al-Arab river by using the seven molluscs species as bioindicators. These species are: snails Lymnaea auricularia, Theodoxus jordani, Physa acuta, Melanopsis nodosa, and Melanoides tuberculata and bivalves Corbicula fluminea and Corbicula fluminalis. The species of molluscs are collected from different locations of the Shatt Al-Arab river (along the region extended from Abu Al-Khasib to Garmat-Ali) during 2004 and 2005. Each species consisted of at least 3500 adult of individuals of uniform sizes. The hydrocarbons from these species were extracted and analyzed both by spectroflurometer (total hydrocarbons) and high resolution capillary gas chromatography (n-alkanes). The concentrations of total hydrocarbons in mollusc’s species of the Shatt Al-Arab river ranged from 1.93 μg/g dry weight in T. jordani to 26.56 μg/g dry weight in C. fluminea. The range of carbon chain length of n-alkanes in these individuals was ranging from C13 - C32. The bimodal distribution with two maxima around C17 and C27 suggested two different sources of hydrocarbons both biogenic and anthropogenic. The dominance of the odd carbon numbers n-alkanes (C15, C17, C25 and C29) in the mollusc’s species indicated biogenic origin of hydrocarbons .The pristane values were more than those of phytane. Pristane and phytane in the mollusc’s species suggest biogenic origin. CPI values are more than one indicating a biogenic origin of hydrocarbons in these species. Squalane is also present in some these species intimately related to anthropogenic sources of hydrocarbons. The presence of Unresolved Complex Mixture (UCM) reflects the anthropogenic sources. The lower fat contents were found in T. jordani (0.33 mg/g) and the higher were in C. fluminea (0.98 mg/g). A significant relationship is found between the fat contents and hydrocarbons concentrations in the tissues of molluscs species (r = 0.8 - 0.9).